Cover Feature: Diquat Based Dyes: A New Class of Photoredox Catalysts and Their Use in Aerobic Thiocyanation (Chem. Eur. J. 22/2023). Issue 22 (15th March 2023) - Meier, Armin; Badalov, Sabuhi V.; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René
Abstract : From diquat to dye‐cat : More than just a herbicide, the reversibly reducible diquat moiety now harnesses the power of the sun. Incorporated into donor–acceptor dyes we developed, as well as into charge–transfer complexes we observed, diquat is enabled to absorb visible light. This allowed the use of these systems in the photocatalytic thiocyanation of various indoles and pyrroles, with air as the oxidant. More information can be found in the Research Article by R. Wilhelm and co‐workers (DOI: 10.1002/chem.202203541 ).